2000
DOI: 10.2307/2648216
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Dynamics, Ethnicity and Condom Use among Low-Income Women

Abstract: HIV prevention and intervention programs should emphasize birth control discussion between partners and the development of condom-related self-efficacy and negotiation skills, and these programs also should customize prevention messages according to ethnicity and social context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
84
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(97 citation statements)
references
References 27 publications
13
84
0
Order By: Relevance
“…Our study identified HIV risk behaviors reported by African American women that are comparable to those reported in previously published studies, and researchers have made clear that African American women are no more likely to report unprotected sex, multiple sex partners, or drug use than women of other racial and ethnic groups (Gottlieb et al, 2002;Soler et al, 2000;Warren et al, 1998). Our findings suggest the importance of future research to explore social determinants of health, including poverty-related risk factors such as unstable housing that are likely to influence the vulnerability of African American women to HIV infection (Conwell et al, 2007;Hessol et al, 2001).…”
Section: Discussionsupporting
confidence: 71%
“…Our study identified HIV risk behaviors reported by African American women that are comparable to those reported in previously published studies, and researchers have made clear that African American women are no more likely to report unprotected sex, multiple sex partners, or drug use than women of other racial and ethnic groups (Gottlieb et al, 2002;Soler et al, 2000;Warren et al, 1998). Our findings suggest the importance of future research to explore social determinants of health, including poverty-related risk factors such as unstable housing that are likely to influence the vulnerability of African American women to HIV infection (Conwell et al, 2007;Hessol et al, 2001).…”
Section: Discussionsupporting
confidence: 71%
“…Prior research has found mixed results for the relationship between HIV risk and race/ethnicity. 54,56 For example, more recent studies have shown that Black and Latina women report more consistent condom use compared to White women, 57,58 while an earlier study reported more consistent condom use among White and Latina women. 59 Additional research with drug-involved women is needed to unpack contextual and cultural differences across race and ethnicity in the relationship between power and HIV sexual risk behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…7 Additionally, Soler et al found that women who did not participate in financial decisions were nearly two times less likely to use a condom consistently. 26 Over a century of research has been conducted on social determinants of health, highlighting the importance of social context in shaping health and health behaviors. [27][28][29] Specifically, the decision to use a condom, while often understood as an individual choice, may be strongly impacted by many external factors.…”
Section: Discussionmentioning
confidence: 99%